Revealing the Effectiveness of Government Intern Control Systems in Cash Management for Fraud Prevention - Alma Fadilah; Ayudia Sokarina; Indria Puspitasari Lenap (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2023)
This study aims to reveal the potential for fraud in the Internal Control System for cash receipts and disbursements conducted by BPS Regency X. The research method used is descriptive research method with a qualitative approach. The informants in this study consisted of three people, namely the head of the general subdivision who doubled as the official signing the payment order, the commitment making officier, and the expenditure treasurer of BPS Regency X. The results of this study indicate that BPS Regency X is good at managing its cash, judging from implementation of the Government Internal Control System which is in accordance with the provisions of Government Regulation of the Republic of Indonesia Number 60 of 2008 which identifies that there is no potential for fraud related to receipts and disbursements cash at BPS Regency X